2021
DOI: 10.1016/j.scitotenv.2021.147213
|View full text |Cite
|
Sign up to set email alerts
|

Increases in noise complaints during the COVID-19 lockdown in Spring 2020: A case study in Greater London, UK

Abstract: Many cities around the world have claimed that the enforcement of lockdown measures to contain the spread of COVID-19 and the corresponding limitations of human activities led to reduced environmental noise levels. However, noise complaints reported by many local authorities were on the rise soon after the local lockdowns came into force. This research took Greater London in the UK as a case study. The overall aim was examining how noise complaints changed during the first stages of the lockdown implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 44 publications
4
30
1
Order By: Relevance
“…Likewise, Bartalucci et al [15] in another online survey conducted in Italy during different stages of COVID-19-related lockdowns reported an overall reduction in terms of noise annoyance that was likely induced by the limitation of traffic flows and human activities, which in turn led to improved soundscape assessments. On the other hand, studies focusing on the perception of acoustic environments for people forced to stay home occasionally highlighted negative outcomes, such as increased noiseinduced psychological stress or increased rates of noise complaints (e.g., [16,17]).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Bartalucci et al [15] in another online survey conducted in Italy during different stages of COVID-19-related lockdowns reported an overall reduction in terms of noise annoyance that was likely induced by the limitation of traffic flows and human activities, which in turn led to improved soundscape assessments. On the other hand, studies focusing on the perception of acoustic environments for people forced to stay home occasionally highlighted negative outcomes, such as increased noiseinduced psychological stress or increased rates of noise complaints (e.g., [16,17]).…”
Section: Introductionmentioning
confidence: 99%
“…Still, greater exposure to mechanical noise during home confinement contributed consistently to a resident's worse self-reported health, whereas nature sounds correlated with greater restorative capacity of the home; however, those dwellers having soundproof windows installed in their homes, and therefore more acoustic comfort, reported better overall wellbeing independently associated [153]. In contrast, where construction/public work and neighbourhood noise was reported to become an annoyance for residents, housing characteristics were an important factor of indoor acoustic environment and complaints during lockdown [164,165].…”
Section: Housing Design and Constructive Characteristics Impact On Environmental Conditionsmentioning
confidence: 94%
“…It mitigates the impact of the crisis on businesses and generates profits. Tong et al [32] declare that a quarter of people currently shop more online and 15% of the UK population say they spend a lot of time using streaming services. Hao et al [33] focused on research of the impact of online commerce on shopping behavior and they revealed that these channels need to be improved efficiently to support pandemic policies.…”
Section: Literature Reviewmentioning
confidence: 99%